The study on customer satisfaction towards credit card / Nurliana Omar - Omar, Nurliana (Faculty of Business and Management, 2011)
This project paper is prepared as a partial fulfilment of the Bachelor Administration (BBA) majoring in Finance. Due to this purpose, I have determined the topic of my research study that relate between marketing and finance area which is “A study on customer satisfaction towards credit card”. This study is focused more on which factor can be satisfied customer on using credit card either reliability, quality service or features of credit card itself. This project paper contains five chapters. It includes an introduction, literature review, research methodology, finding and analysis, conclusion and recommendation. The project paper will present a research on customer satisfaction towards credit card. Total numbers of respondents are 50 respondents based on sampling method of simple random sampling technique in order to gather the related information to this research. The target population of the study is people who live at Kuala Selangor and have experience with credit card. From the result of the study, it indicates that quality of service provided by banks is the factor that make customer satisfied. As the conclusion, bank needs to maintain with their service and make it more excellent rather than now to make customer become more satisfy and stay longer with them.